Development of a complete spin filter for metastable hydrogen atoms and its isotopes - N. Faatz; R. Engels; C. Kannis; B. Breitkreutz; H. Soltner (Physics Open)
Since the early days of quantum mechanics, hydrogen, as the simplest of all atoms, has been studied or used to investigate new physics. In the past this knowledge has been applied to develop a polarimeter where the initial nuclear polarization of a proton beam could be determined. The key component of this Lamb-shift polarimeter is the so called spin filter, which is able to separate one of four metastable hydrogen hyperfine states by quenching the remaining three hyperfine states to the ground state. Unfortunately, the conventional spin filter is only able to filter two out of the four hyperfine states individually. Therefore, this work provides the necessary theory as well as experimental conditions to build a new generation of spin filter which permits the separation and transmission of any metastable hydrogen hyperfine state as well as for its isotopes in a corresponding beam. This knowledge is applicable for other experiments in different fields of research, e.g. the bound beta decay, axion research or parity violation experiments.